INFLUENCE OF ENTREPRENEURIAL PASSION, GOVERNMENT SUPPORT, AND LEARNING CAPABILITY ON THE PERFORMANCE OF CREATIVE SMEs IN JEMBER DISTRICT - Lilik Farida; Ariwan Joko Nusbantoro; Chairul Saleh; Ketut Indraningrat; Elok Sri Utami; Nadia Azalia (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2023)
: This study examines the influence of three dimensions of entrepreneurial passion, namely a passion for inventing, passion for developing, and passion for founding, on the performance of creative industry-based MSMEs in Jember, Indonesia, after the Covid-19 pandemic with government support and learning capability as a moderating variable. Using a purposive sampling technique, as many as 280 creative MSMEs in Jember were involved in this study. Based on the results of the SEM-PLS analysis, passion for inventing and passion for developing have a significant positive effect on MSME performance. Learning capability can strengthen the influence of passion for inventing and passion for developing MSME performance. This study did not find a significant effect of passion for founding on MSME performance, and government support could not strengthen the influence of passion for inventing, developing, and founding on MSME performance. In addition, this study found that learning capability cannot strengthen the influence of passion for founding on MSME performance. The findings of this study offer theoretical and practical implications regarding how important the entrepreneurial spirit is in improving MSME performance after the Covid-19 pandemic by increasing learning capability in the creative industry-based MSME sector.